Performance Evaluation of Optimized Resource Allocations in WDM Networks under Dynamic Traffic - Yu, Shen (University of Ottawa (Canada), 2010)
Wavelength-routed Wavelength-Division Multiplexing (WDM) optical networks are developed to meet the increasing bandwidth demands of recent Internet applications. In the real world, the traffic demands are always dynamic. The question of how to optimally allocate the network resources in a wavelength-routed WDM optical network to satisfy dynamic demands is called the dynamic routing and wavelength assignment (RWA) problem. In the literature, many schemes are proposed to address this problem. In this thesis, we study how to improve the performance of certain dynamic RWA schemes by using the distribution of the dynamic demands, which is assumed to be known in advance. With the knowledge of the network topology and distribution of the dynamic traffic, we can use an existing mathematical approach to calculate, for each link, a cost value called Multiplier Guide. This link cost is obtained by considering a static RWA optimization problem having the average traffic demands of the dynamic RWA problem that we want to solve. When this link cost is used instead of the hop count to compute minimal cost paths, the performance of some dynamic RWA schemes can be improved, as shown by our simulation studies. In the thesis, we review and implement several existing dynamic RWA schemes; we also propose and implement some new dynamic RWA schemes. We apply the Multiplier Guide to all these schemes and run simulations to test whether their performance is improved. As a necessary part of these schemes, we implement many different network routing algorithms including single shortest path routing, link-disjoint paths routing and k-shortest paths algorithm. To simulate the schemes that search an RWA solution exhaustively with or without the wavelength conversion assumption, we implement two auxiliary graphs and two algorithms associated with the graphs, respectively. We also implement the schemes that use link utilization obtained from simulations or measurements to decide link cost; and we compare them with the schemes that use the Multiplier Guide as link cost. We find that, when the Multiplier Guide is applied to the dynamic RWA schemes that use pre-constructed paths, their performance is improved. However, when the Multiplier Guide is applied to the schemes that search an RWA solution exhaustively, their performance is not improved.
Keywords: Engineering, Electronics and Electrical.